Comparison of slaughter and carcass characteristics of ram, wether and ewe market lambs - Kropf, Donald H.; Mackintosh, D.L.; Hinnergardt, L.C.; Menzies, C.S.; Harrison, D.L.; Anderson, L. (Kansas Agricultural Experiment Station, 2011)
Lambs sired by Hampshire rams and from western ewes were individually slaughtered as they reached 96 lbs. live weight. Quality and quantity factors were evaluated after carcasses were chilled 48 hours. Carcasses were broken into wholesale cuts and weights obtained. The leg and loin were trimmed of external fat in excess of 3/8 inch and trimmed weights were taken. Ewe lambs dressed heavier carcasses and a higher dressing %,' but the extra carcass weight was due to higher finish. Wether and ewe lamb carcasses showed higher conformation scores and higher U.S.D.A. grades, apparently due to more fat. Fat and lean from ram carcasses was noticeably less firm than from wethers and ewes. Lowest rib eye marbling scores were noted in ram carcasses, highest scores in ewe carcasses, with intermediate values in wethers.
Keywords: Lamb; Carcass characteristics; U.S.D.A. grades; Marbling scores